2019
DOI: 10.1016/j.compedu.2019.103612
|View full text |Cite
|
Sign up to set email alerts
|

Applications of data science to game learning analytics data: A systematic literature review

Abstract: Data science techniques, nowadays widespread across all fields, can also be applied to the wealth of information derived from student interactions with serious games. Use of data science techniques can greatly improve the evaluation of games, and allow both teachers and institutions to make evidence-based decisions. This can increase both teacher and institutional confidence regarding the use of serious games in formal education, greatly raising their attractiveness. This paper presents a systematic literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 82 publications
2
61
0
1
Order By: Relevance
“…Finally, authors in [35] conducted a systematic literature review, analyzing 87 papers that reported evidence of the outcomes of the analysis of game analytics data and/or learning analytics data collected from serious games. Authors concluded that the application of data science can increase the still-limited application of serious games in education.…”
Section: B Learning Analytics and Metricsmentioning
confidence: 99%
“…Finally, authors in [35] conducted a systematic literature review, analyzing 87 papers that reported evidence of the outcomes of the analysis of game analytics data and/or learning analytics data collected from serious games. Authors concluded that the application of data science can increase the still-limited application of serious games in education.…”
Section: B Learning Analytics and Metricsmentioning
confidence: 99%
“…The latest literature review is provided by Alonso-Fernández et al [8]. They systematically summarize the research progress of applying data science and technology to serious game analytics to support decision making.…”
Section: Foundationmentioning
confidence: 99%
“…The reason why we exclude the research on serious games as the previous literature review on this area already exists [8]. As shown in Fig.…”
Section: • Exclusion Criteriamentioning
confidence: 99%
“…Regarding the analysis to be performed on the collected data, the sample size restricts the application of artificial intelligence techniques as they require a high amount of data. However, comparing our work with the applications of data science to game and learning analytics data in general contexts [20], we consider that the sample size reached for participants with intellectual disabilities is highly representative. The number of students with ID in each classroom is substantially lower compared with other ordinary educational environments.…”
Section: Related Workmentioning
confidence: 99%